INCREASING PUBLIC AWARENESS OF HEPATITIS B DISEASE IN GONDANGLEGI, MALANG REGENCY - Supriono, Supriono; Wibowo, Bogi Pratomo; Mustika, Syifa; Fachrureza, Mochamad (Caring: Jurnal Pengabdian Masyarakat, 2023)
AbstractHepatitis B is an illness resulting from the hepatitis B virus, which can spread through both horizontal and vertical transmission. According to the World Health Organization (WHO) in 2019, approximately 296 million individuals across the globe were afflicted with hepatitis B, with an anticipated annual increase of 1.5 million cases. Various approaches and solutions have been implemented to prevent and address the impact of this disease, including hepatitis B immunization policies from birth. According to the Regulation of the Minister of Health No. 25 of 2015, other approaches are also being pursued through health promotion using various media. This study aims to determine the effectiveness and factors related to public knowledge about hepatitis B through interactive educational media for the community in Gondanglegi Village, Malang Regency. A total of 176 respondents completed the questionnaire, with 75% being female and 24% male. The majority of respondents fell within the age range of 51-60 years (34.7%). The Wilcoxon test results show a significant difference between pre-test and post-test scores (p=0.000). The Spearman test, which relates age and the last level of education to pre-test and post-test scores, reveals a significant relationship between pre-test scores and age (p=0.000, r=-0.458) as well as the last level of education (p=0.000, r=0.472). The correlation analysis results indicate that older age is associated with lower pre-test scores, while higher levels of education are associated with higher pre-test scores. A similar pattern is observed in the correlation test between post-test scores and age (p=0.082, r=-0.204) and the last level of education (p=0.013, r=0.013). These results indicate that the community engagement program to increase awareness of hepatitis B has successfully improved participants' knowledge, as reflected in the difference between pre-test and post-test scores.